Intersubband transitions and anneal-induced interdiffusion effects in III-V-N quantum wells - Dang, Yuxing (2008)
III-V compounds consisting of nitrogen are candidates for interband transition applications because of their small band gap due to the nitrogen (N) incoporation. In addition, there is renewed interest in their possible applications in intersubband transition based devices owing to its large conduction band offset.